Bioacoustics for species management: two case studies with a Hawaiian forest bird. Issue 20 (5th October 2015) - Sebastián‐González, Esther; Pang‐Ching, Joshua; Barbosa, Jomar M.; Hart, Patrick
Abstract: The management of animal endangered species requires detailed information on their distribution and abundance, which is often hard to obtain. When animals communicate using sounds, one option is to use automatic sound recorders to gather information on the species for long periods of time with low effort. One drawback of this method is that processing all the information manually requires large amounts of time and effort. Our objective was to create a relatively "user‐friendly" (i.e., that does not require big programming skills) automatic detection algorithm to improve our ability to get basic data from sound‐emitting animal species. We illustrate our algorithm by showing two possible applications with the Hawai'i 'Amakihi, Hemignathus virens virens, a forest bird from the island of Hawai'i. We first characterized the 'Amakihi song using recordings from areas where the species is present in high densities. We used this information to train a classification algorithm, the support vector machine (SVM), in order to identify 'Amakihi songs from a series of potential songs. We then used our algorithm to detect the species in areas where its presence had not been previously confirmed. We also used the algorithm to compare the relative abundance of the species in different areas where management actions may be applied. The SVM had an accuracy of 86.5% in identifying 'Amakihi. We confirmed the presence of the 'Amakihi at the study area using the algorithm. We also found that the relative abundance of 'Amakihi changes among study areas, and this information can be used to assess where management strategies for the species should be better implemented. Our automatic song detection algorithm is effective, "user‐friendly" and can be very useful for optimizing the management and conservation of those endangered animal species that communicate acoustically. Abstract : In this article we describe an automatic detection algorithm to improve our ability to get basic data from sound‐emitting animal species. We show how our algorithm can be used to detect presence and compare relative abundance for the Hawai'i 'Amakihi, a forest bird from the island of Hawai'i. Our automatic song detection algorithm is effective, "user‐friendly" and can be very useful for optimizing the management and conservation of those endangered animal species that communicate acoustically.